Fast Genetic Programming and Artificial Developmental Systems on GPUs - Harding, S.; Banzhaf, W. (HPCS 2007 : 21st International Symposium on High Performance Computing Systems and Applications : 13-16 May 2007, Saskatoon, Saskatchewan, Canada, 2007)
In this paper we demonstrate the use of the graphics processing unit (GPU) to accelerate evolutionary computation applications, in particular genetic programming approaches. We show that it is possible to get speed increases of several hundred times over a typical CPU implementation, catapulting GPU processing for these applications into the realm of HPC This increase in performance also extends to artificial developmental systems, where evolved programs are used to construct cellular systems. Feasibility of this approach to efficiently evaluate artificial developmental systems based on cellular automata is demonstrated.